2019
DOI: 10.20944/preprints201911.0358.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trehalose Protects Maize Plants from Salt Stress and Phosphorus Deficiency

Abstract: This study was undertaken to elucidate the role of trehalose (Tre) in mitigating oxidative stress under salinity and low P in maize. Eight-day-old maize seedlings of two maize varieties, BARI Hybrid Maize-7 and BARI Hybrid Maize-9 were subjected to salinity (150 mM NaCl), low P (5 µM KH2PO4) and their combined stress with or without 10 mM Tre for 15-d.Salinity and combined stress significantly inhibited the shoot length, root length, and root volume, whereas, low P increased the root length and volume in both … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…A non-targeted metabolic profiling of six legume plants in the Lotus genus under drought conditions revealed a significant increase in trehalose abundance across all species tested 89 . In maize, external trehalose treatment enhanced antioxidant activities under high salinity and P-deficient conditions, thus achieving better seedling growth 90 . Genetically modified rice plants that over-expressed a fusion gene encoding both Escherichia coli Trehalose-6-phosphate synthase and Trehalose-6-phosphate phosphatase, which are responsible for trehalose biosynthesis, exhibited 200-fold greater accumulation of trehalose and significantly higher tolerance to drought, salinity, and cold stress 91 .…”
Section: /44mentioning
confidence: 99%
“…A non-targeted metabolic profiling of six legume plants in the Lotus genus under drought conditions revealed a significant increase in trehalose abundance across all species tested 89 . In maize, external trehalose treatment enhanced antioxidant activities under high salinity and P-deficient conditions, thus achieving better seedling growth 90 . Genetically modified rice plants that over-expressed a fusion gene encoding both Escherichia coli Trehalose-6-phosphate synthase and Trehalose-6-phosphate phosphatase, which are responsible for trehalose biosynthesis, exhibited 200-fold greater accumulation of trehalose and significantly higher tolerance to drought, salinity, and cold stress 91 .…”
Section: /44mentioning
confidence: 99%
“…The ASA-GSH pathway comprises four enzymes, namely, APX, MDHAR, DHAR and GR (Raja et al 2017) and plays a key role in ROS detoxification by regulating intracellular levels of H 2 O 2 (Hasanuzzaman et al 2019;Raja et al 2020). In higher plants, H 2 O 2 is produced predominantly in the chloroplasts and peroxisomes, in which APX is widely distributed and reduces H 2 O 2 to H 2 O via the oxidation of ASA, thereby protecting these structures from oxidative damage (Rohman et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The ASA-GSH pathway comprises four enzymes, namely, APX, MDHAR, DHAR and GR (Raja et al 2017) and plays a key role in ROS detoxification by regulating intracellular levels of H 2 O 2 (Hasanuzzaman et al 2019;Raja et al 2020). In higher plants, H 2 O 2 is produced predominantly in the chloroplasts and peroxisomes, in which APX is widely distributed and reduces H 2 O 2 to H 2 O via the oxidation of ASA, thereby protecting these structures from oxidative damage (Rohman et al 2019). The two Chl APX isogenes tAPX and sAPX are located in the thylakoid membrane and chloroplast stroma, respectively (Qiu et al 2020), the former of which is highly sensitive to exogenous H 2 O 2 (in contrast to sAPX) (Li 2014), and its expression is rapidly suppressed during senescence (Panchuk et al 2005 (Li 2014), and in the present study, we found that the expression of APX6 and APX3 (peroxisome APX) was significantly repressed during leaf senescence, whereas that of APX7 and APX2 (cytoplasmic APXs) was gradually up-regulated concomitant with H 2 O 2 accumulation during late senescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation